О преимуществах применения гетеродинирования в частотном измерителе наноразмеров - Данелян, А. Г.; Мачехин, Ю. П.; Гарибашвили, Д. И.; Данелян, А. Г.; Канкия, Р. Р.; Мкртычан, С. А.; Шоташвили, С. В. (ХНУРЭ, 2010)
В данной работе предлагается определённая модернизация устройства, реализующего частотный метод измерений, которая может позволить упростить конструкцию, сохранив его точностные характеристики. Work represents development of the previous researches of authors on creation of a frequency measuring instrument of the nano-scale dimensions, an alternative to methods of laser interferometry of displacements. Expected resolution of the offered method is of the order of 0.5 picometers. In the report it is offered to use heterodyne method for carry of frequencies of signals on frequency of the standard frequency. It can essentially simplify a design of the device (there is no necessity for additional adjustable optical delays). Use of the precision comparator of frequencies should keep metrological characteristics and opportunities of the device.
Keywords: измерение наноразмеров; лазерная интерферометрии перемещений; замкнутая оптическая задержка; генератор оптического меандра